The expression `cos(2*sin^-1(x))` has to be expressed as an algebraic expression in x.

`cos(2*sin^-1(x))`

=> `1 - 2*sin^2(sin^-1(x))`

=> `1 - 2*(sin(sin^-1(x))^2`

=> `1 - 2*x^2`

**The expression `cos(2*sin^-1(x))` can be written as **`1 - 2*x^2`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now